The effect of expectancy on conditioned pain modulation: evidence from functional near-infrared spectroscopy - Li, Xueshan; Liu, Min; Liu, Bo; Yue, Heng; Cheng, Xiangjuan; Bao, Hugejiletu (Frontiers in Psychology, 2025)
Background and objectiveThe psychological mechanisms that make Conditioned Pain Modulation (CPM) an effective non-pharmacological intervention are still not fully understood. Expectancy is believed to be a critical psychological factor affecting CPM effects, but its specific role has yet to be fully clarified. This study aims to explore the relationship between expectancy and CPM while providing physiological evidence using functional near-infrared spectroscopy (fNIRS).MethodA standardized CPM induction paradigm was implemented, with verbal guidance used to induce expectancy. The Numeric Rating Scale (NRS) assessed the intensity of the test stimulus (TS), while an 11-point scale evaluated participants’ attentional focus on the TS and the effect of expectancy. fNIRS was employed to monitor changes in prefrontal cortex (PFC) activity.ResultsExpectancy significantly amplified the CPM effect (p = 0.036) while markedly reducing attention to the experimental stimulus (p = 0.004). fNIRS findings indicated significant reductions in activity within the left frontal eye field, left dorsolateral prefrontal cortex, and left frontal pole regions. In the post-test, the control group demonstrated significantly higher cortical activity in the right frontal pole region compared to the expectancy group (p < 0.05). Within the expectancy group, bilateral frontal pole cortical activity was significantly lower in the post-test compared to the pre-test (p < 0.05).ConclusionExpectancy represents a key psychological mechanism underlying the CPM effect, potentially modulating its magnitude through attention regulation and accompanied by a reduction in oxygenated hemoglobin activity in the frontal pole region and introduced the Expectancy-Attention-CPM Modulation Model (ECAM).